2016
DOI: 10.1007/s00441-016-2440-8
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of collagen adhesion receptors to tissue fibrosis

Abstract: Fibrosis is the result of a wound-healing response that fails to restore normal tissue structure function. One of the critical hallmarks of fibrosis is disrupted collagen remodeling. In tissue homeostasis, the production, deposition and organization of collagen is balanced by the degradation and remodeling of collagen within the existing matrix. After injury or chronic infection, tissues initiate a wound-healing response that is intended to create a new ECM for restoring tissue structure and function. If the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 183 publications
(217 reference statements)
0
52
0
Order By: Relevance
“…Collagen is the most abundant mammalian protein, and it plays major roles in cellular function . For example, collagen I is a major ECM component produced by fibroblasts during wound healing, and collagen IV is involved in various cellular interactions . The adhesion study showed that collagen I and IV played the most critical roles in terms of hDMC adhesion among the ECM components evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collagen is the most abundant mammalian protein, and it plays major roles in cellular function . For example, collagen I is a major ECM component produced by fibroblasts during wound healing, and collagen IV is involved in various cellular interactions . The adhesion study showed that collagen I and IV played the most critical roles in terms of hDMC adhesion among the ECM components evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Naïve hDMCs expressed higher levels of α 1 and α 2 β 1 than α IIb β 3 and α V β 3, and co‐culture hDMCs expressed higher levels of α 2 β 1 and α IIb β 3 compared with naïve hDMCs. Integrin α 2 β 1 has a higher affinity for collagen I than for collagen IV, and integrin α 1 binds more strongly to collagen IV than to collagen I . Previous studies showed that α 2 β 1 deletion in mice reduced collagen binding and delayed platelet aggregation, triggering immediate developmental defects, but α 1 deletion simply reduced tumor vascularization without any obvious immediate developmental defect .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, observations revealed a potent effect of MGO‐treated collagen on FN protein levels and assembly. Biologic effects may derive from this change in content and organization of this glycoprotein 36 . Increased assembly of FN molecules stimulates deposition of Type I collagen fibrils, promoting development of fibrosis 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Chronic wound healing is usually observed in susceptible subjects such as elders and diabetics among others (Posnett & Franks, ). Conversely, excessive healing can lead to the accumulation of a scar enriched in a densely cross‐linked collagenous extracellular matrix, giving rise to fibrosis (Coelho & McCulloch, ). Fibrosis is an important driver of tissue malfunction in several acute and chronic diseases affecting the heart, liver, kidney, lung, and skin (Coelho & McCulloch, ).…”
Section: The Importance Of Wound Healing In Periodontal Tissuesmentioning
confidence: 99%
“…Conversely, excessive healing can lead to the accumulation of a scar enriched in a densely cross‐linked collagenous extracellular matrix, giving rise to fibrosis (Coelho & McCulloch, ). Fibrosis is an important driver of tissue malfunction in several acute and chronic diseases affecting the heart, liver, kidney, lung, and skin (Coelho & McCulloch, ). In global terms, fibrosis contributes to about 33% of the deaths in developed countries (Hinz, ).…”
Section: The Importance Of Wound Healing In Periodontal Tissuesmentioning
confidence: 99%